Studies of the sliding spark discharge in gas at atmospheric pressure - Berezina, G.P.; Yegorov, A.M.; Karas, V.I.; Us, V.S. (Вопросы атомной науки и техники, 2000)
The aim of the study is to develop physical principles and methods of calculating efficient plasma-chemical reactors based on a sliding discharge at atmospheric pressure with pumping a gas mixture to decompose harmful compounds and to synthesize the compounds of use, and also to develop various ecologically clean processes. The necessity of wide-scale theoretical and experimental investigations, into the atmospheric-pressure gas discharge stems from: i) the importance for solving ecological and technological problems and ii) its inadequate study, as opposed to the case of discharges with tens of torrs, because of the difficulties of using the existing diagnostic facilities and even the methods of measurements at these parameters. Studies were made into gas-dynamic and electrodynamic characteristics of TSD-based plasma-chemical reactors at positive and negative polarities of supply voltage applied to the wire-like electrode and for different rates of air flow through the reactors at different pressures inside the plasma-chemical chamber. The studies were made to optimize the plasma-chemical reactor design and to investigate the influence of different polarities of supply voltage to the wire electrode on the performance of the devices under consideration. The electrodynamic SD characteristics were taken by the standard technique using standard instrumentation. The radiation spectra of high-pressure TSD were studied with an aid of the diffraction spectrograph DFS-452, the spectrograph SP 51, the diffraction monochromator MDR-12U and the photomultiplier tube PMT-39A in the 200 to 600 nm range.